2019
DOI: 10.2519/jospt.2019.0301
|View full text |Cite
|
Sign up to set email alerts
|

Hand Pain and Sensory Deficits: Carpal Tunnel Syndrome

Abstract: When examining a patient with suspected carpal tunnel syndrome (CTS), clinicians should use Semmes-Weinstein monofilament testing (SWMT), using the 2.83 or 3.22 monofilament as the threshold for normal light touch sensation and static 2-point discrimination on the middle finger to aid in determining the extent of nerve damage. In those with suspected moderate to severe CTS, clinicians should assess any radial finger using the 3.22 filament as the threshold for normal. Semmes-Weinstein monofilament testing shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 287 publications
4
52
0
3
Order By: Relevance
“…For mild to moderate CTS, therapy usually includes advice, splinting, electrophysiological agents as well as manual therapy and/or exercises. 51 There is currently limited evidence for a short-term benefit of splinting compared to no treatment. 113 Splinting is recommended at night only.…”
Section: Natural History Prognosis and Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…For mild to moderate CTS, therapy usually includes advice, splinting, electrophysiological agents as well as manual therapy and/or exercises. 51 There is currently limited evidence for a short-term benefit of splinting compared to no treatment. 113 Splinting is recommended at night only.…”
Section: Natural History Prognosis and Managementmentioning
confidence: 99%
“… 113 Splinting is recommended at night only. 51 A Cochrane review reported that there is limited evidence for a beneficial effect of exercise and mobilisation in the management of patients with CTS. 114 This was supported by another review suggesting that neural mobilisation did not improve clinical outcomes compared to other treatments.…”
Section: Natural History Prognosis and Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Its prevalence in the United States working population is 7.8% [ 1 ], with higher and increasing incidence in the industrial sector than in the general population [ 2 , 3 ]. Classic CTS symptoms and sensorimotor alterations include nocturnal pain associated with tingling, numbness, and - in more severe cases - weakness in the median nerve territory that affects the hand motor control, especially during activities involving the first three fingers [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A thorough history and physical examination are the key to diagnosis [ 4 ]. Thenar atrophy [ 6 ] and sensory loss [ 7 ] are common findings, but not always present in the early stages of the disease [ 4 , 8 ] and unable to rule out CTS [ 9 ]. Provocative tests aimed at reproducing the patient’s symptoms - such as the Phalen’s test and Tinel’s sign - are often used in the clinical setting, but there is no evidence to support their use as independent diagnostic tools [ 9 ].…”
Section: Introductionmentioning
confidence: 99%